Estudo das propriedades estruturais, eletrônicas e termoelétricas de nanofios de PbSe e PbTe - Wrasse, Ernesto Osvaldo (2013)
In this work we study simultaneously the structural, electronic and thermoelectric properties of PbSe and PbTe nanowires, analyzing the quantum confinement effects, the dependence with the planar stoichiometry and the spin-orbit interactions. We also study these nanowires in the presence of intrinsic defects (vacancies and antisites) and doped with group III (Al, Ga, In, and Tl) impurity. We use first principles calculations within the formalism of the density functional theory (DFT). We observed that the nanowires are more stable in the rock salt structure and aligned along the (001) direction. The electronic properties of nanowires are in uenced by three effects: the quantum confinement, spinorbit interactions and the planar stoichiometry. The quantum confinement increases the thermoelectric efficiency of the PbSe and PbTe nanowires when compared to the system in the bulk phase, reaching an increase up to two orders in the magnitude, leading the PbSe and PbTe nanowires with great potential to be used in thermoelectric devices. We studied the in uence of intrinsic defects and group III impurity doping in the main properties of PbSe and PbTe, we show that these defects give rise to different electronic properties in the nanowires as compared to the bulk one. Intrinsic defects and group III impurities, which modify the electronic density of states (DOS) near to the top of the valence band or near to the bottom of the conduction band increase the thermoelectric efficiency of the PbSe and PbTe nanowires. However, defects that introduce electronic levels in energy band gap are shown to cause and degradation in the thermoelectric efficiency. The increase (decrease) in thermoelectric efficiency is associated with a lower (higher) value of electronic part of the thermal conductivity. In summary, we show that PbSe and PbTe nanowires are very promising materials to be used in thermoelectric, electronic and optical devices.